2016
DOI: 10.1177/0193945916635573
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Progressive Muscle Relaxation Therapy in Colorectal Cancer Patients

Abstract: This study aimed to examine the effect of progressive muscle relaxation therapy (PMRT) on cortisol level, the Stress Arousal Checklist (SACL) score, blood pressure, and heart rate in colorectal cancer patients undergoing laparoscopic surgery. Forty-six patients were divided into control and experimental groups. Cortisol levels, blood pressure, and heart rate were measured before surgery and between 8:00 and 11:00 a.m. on the first, third, and fifth days after surgery. SACL score was measured before surgery and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 23 publications
(24 reference statements)
2
15
0
11
Order By: Relevance
“…Besides, PMR affects reducing anxiety, improving quality of life, and creating appropriate coping mechanisms in problem-solving situations (12). performing pMr consists of a 20-minute systematic relaxation of ten different muscle groups accompanied by deep breathing exercises (12,13). pMr is proven to be an easily applicable method with no side effects while successfully reducing the side-effects of medical treatments in cancer patients, affecting hemodynamic profile, reducing stress, and anxiety, thus improving the quality of life (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, PMR affects reducing anxiety, improving quality of life, and creating appropriate coping mechanisms in problem-solving situations (12). performing pMr consists of a 20-minute systematic relaxation of ten different muscle groups accompanied by deep breathing exercises (12,13). pMr is proven to be an easily applicable method with no side effects while successfully reducing the side-effects of medical treatments in cancer patients, affecting hemodynamic profile, reducing stress, and anxiety, thus improving the quality of life (13).…”
Section: Discussionmentioning
confidence: 99%
“…performing pMr consists of a 20-minute systematic relaxation of ten different muscle groups accompanied by deep breathing exercises (12,13). pMr is proven to be an easily applicable method with no side effects while successfully reducing the side-effects of medical treatments in cancer patients, affecting hemodynamic profile, reducing stress, and anxiety, thus improving the quality of life (13). Cheung et al have shown the statistically significant effect of pMr on reducing anxiety in postoperative patients with colorectal cancer after stoma surgery (12).…”
Section: Discussionmentioning
confidence: 99%
“…HR menurun signifikan pada hari 1 dan hari ke 5 pasca operasi. Sedangkan TD (sistolik dan diastolik) menurun signifikan pada hari ke 3 dan hari ke 5 pasca operasi (13) .…”
Section: Hemodinamikunclassified
“…Penelitian pengaruh PMR terhadap kortisol yang diukur sebelum dan sesudah operasi kolorektal menunjukkan kortisol pada grup kontrol hari pertama, ketiga dan kelima pasca operasi lebih tinggi dibandingkan grup intervensi (13) . Peningkatan hormon kortisol dalam tubuh diyakini mempengaruhi derajat nyeri pada pasien pasca operasi.…”
Section: Hormon Kortisolunclassified
See 1 more Smart Citation